The Influence of Brand Image, Trust, Perceived Value, and Electronic Word of Mouth on Purchase Decisions for Hanasui Products on TikTok Shop - Akhila Fatmawati; Ady Achadi; Enrico Aziezy; Dian Safitri P Koesoemasari (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid growth of TikTok Shop as a social commerce platform has reshaped consumer purchasing behavior in the beauty industry, particularly by integrating product promotion, peer interaction, and transaction processes within a single digital environment. However, the determinants of purchase decisions for local cosmetic products on TikTok Shop remain underexplored. This study aimed to examine the effects of brand image, trust, perceived value, and electronic word of mouth (e-WOM) on consumers’ purchase decisions regarding Hanasui products on TikTok Shop. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires from 100 Hanasui consumers in Purwokerto who had purchased products through TikTok Shop, using purposive sampling. The data were analyzed using multiple linear regression. The findings reveal that brand image, trust, perceived value, and e-WOM have positive and significant effects on purchase decisions, with perceived value emerging as the most influential predictor. Collectively, these four variables explain 50.7% of the variance in purchase decisions. The study concludes that consumers’ purchase decisions in social commerce environments are shaped by brand perception, consumer trust, perceived product value, and digital information generated through online interactions. These findings contribute to the literature on social commerce and digital consumer behavior by demonstrating the combined role of cognitive, relational, and informational factors in cosmetic product purchase decisions, while offering practical implications for companies to strengthen brand image, enhance trust, optimize product value, and manage e-WOM more effectively.